ANALYSIS OF RECIPROCAL BETWEEN ONLINE TRANSPORTATION BUSSINESS WITH BEHAVIOR MOVEMENT OF MALANG PEOPLE'S CONSUMPTION ON SOCIETY PURCHASING POWER PARITY - Naufal Atha Haidarbahy (AIBPM Publisher, 2018)
This paper describes the relationship of online transportation circulating in the middle of Malang society which has been predisposing on the mobility or the movement of Malang residents in dailytime and the reciprocity when it’s affects the ability of the Malang residents to pay attention to this online transportation. Study in this field tend to the problem of consumer habits in conducting consumption activities on spending the sale value of online transportation services. In this analysis there are variables that affect this as customer experience, brand loyalty, disruption from conventional to non-conventional and custom-in-decision. The purposes of this study are providing description and the right policy direction in responding lifestyle changes that can be spelled out complexly and very global both to the policy makers and the general public. The population of this study is the online transport consumer in Malang with a sample of all statistical data about online transport and public opinion. The analytical technique that the writer used is qualitative descriptive method which is useful to give and explain facts and data. Communities in mobilization need tools where they want to be fast and precise with perfect quality because today's digital age demands us to be more adaptive and more innovative to survive each other, especially in the daily activities that are assisted by online transport. This online transportation has even fundamentally shaped the society's influential consumption behavior in its daily life in mobilizing to meet its needs. Keywords: consumer behavior, purchasing power, society habit, online transportation